ANALISIS KAPASITAS DRAINASE MENGGUNAKAN PERANGKAT LUNAK HEC-RAS VERSI 6.0 DALAM MITIGASI BANJIR PERKOTAAN STUDI KASUS: JALAN TRANS BARELANG - Natasya Aurum Maharani; Ade Jaya Saputra; Jody Martin Ginting (LPPM Universitas Abdurrab, 2025)
The occurrence of extreme rain with an intensity of 294.8 mm/day caused flooding in Batam City. This resulted in the Trans Barelang Road experiencing inundation due to the inability of the channel to accommodate flow discharge. The purpose of this study is to analyze the capacity of drainage channels using Hec-ras software version 6.0. The research method was carried out with a quantitative approach. The analysis using the maximum rainfall for a 10-year period with a time span of 2014-2023 resulted in a planned discharge with a 2-year re-period, of 11,195 m³/s. The results of the simulation of the existing channel using Hec-ras software with dimensions of 1.4 x 1.2 m show a water surface elevation of 1.95 m which exceeds the channel elevation limit. This results in runoff in the channel. For this reason, it is necessary to change the dimensions of the channel so that it can accommodate the flow discharge as a repair step. The results of the analysis of the change in the dimensions of the channel with dimensions of 1.5×2.5 m are able to accommodate the planned flow discharge. The maximum water elevation surface (WSE) is 1.78 m, and provides a guard height of 0.78 m. The change in the dimensions of this channel is expected to drain the drainage capacity properly and it is necessary to maintain the channel to prevent a reduction in the channel's discharge capacity